Trained hypertensive rats exhibit decreased transcellular vesicle trafficking, increased tight junctions’ density, restored blood-brain barrier permeability and normalized autonomic control of the circulation - Candido, Vanessa B.; Perego, Sany M.; Ceroni, Alexandre; Metzger, Martin; Colquhoun, Alison; Michelini, Lisete C. (Frontiers in Physiology, 2023)
Introduction: Chronic hypertension is accompanied by either blood-brain barrier (BBB) leakage and autonomic dysfunction. There is no consensus on the mechanism determining increased BBB permeability within autonomic areas. While some reports suggested tight junction’s breakdown, others indicated the involvement of transcytosis rather than paracellular transport changes. Interestingly, exercise training was able to restore both BBB permeability and autonomic control of the circulation. We sought now to clarify the mechanism(s) governing hypertension- and exercise-induced BBB permeability. Methods: Spontaneously hypertensive rats (SHR) and normotensive controls submitted to 4-week aerobic training (T) or sedentary protocol (S) were chronically cannulated for baseline hemodynamic and autonomic recordings and evaluation of BBB permeability. Brains were harvested for measurement of BBB function (FITC-10 kDa leakage), ultrastructural analysis of BBB constituents (transmission electron microscopy) and caveolin-1 expression (immunofluorescence). Results: In SHR-S the increased pressure, augmented sympathetic vasomotor activity, higher sympathetic and lower parasympathetic modulation of the heart and the reduced baroreflex sensitivity were accompanied by robust FITC-10kDa leakage, large increase in transcytotic vesicles number/capillary, but no change in tight junctions’ density within the paraventricular nucleus of the hypothalamus, the nucleus of the solitary tract and the rostral ventrolateral medulla. SHR-T exhibited restored BBB permeability and normalized vesicles counting/capillary simultaneously with a normal autonomic modulation of heart and vessels, resting bradycardia and partial pressure reduction. Caveolin-1 expression ratified the counting of transcellular, not other cytoplasmatic vesicles. Additionally, T caused in both groups significant increases in tight junctions’ extension/capillary border. Discussion: Data indicate that transcytosis, not the paracellular transport, is the primary mechanism underlying both hypertension- and exercise-induced BBB permeability changes within autonomic areas. The reduced BBB permeability contributes to normalize the autonomic control of the circulation, which suppresses pressure variability and reduces the occurrence of end-organ damage in the trained SHR. Data also disclose that hypertension does not change but exercise training strengthens the resistance of the paracellular pathway in both strains.